STRATEGI PENINGKATKAN PENERIMAAN RETRIBUSI PELAYANAN PASAR KOTA SERANG - Chandra, Aradea; Rustiadi, Ernan; Hariyoga, Himawan (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2017)
ABSTRACTThe era of regional autonomy requires every region to have independence in managing its regional finance in order to increase its local revenue. Market retribution is a type of retribution that can be potentially used as a source of local revenue. Serang city is one of the cities that become a merchant destination for traders from other regions due to its rapid economic development. The aim of this study is to analyze the performance of market retribution, to analyze the perception of merchants in accordance with the implementation of collection policy and to formulate the strategy to increase market retribution receipts. The primary data was obtained from interviews with the merchants and pertinent institution official that were chosen purposively (purposive sampling). Various analytical methods which were specifically implemented in order to achieve the purpose of the study are as follow: analysis of local government financial performance, descriptive statistical analysis, and analytical hierarchy process. The result of the analysis suggests that: (1) in general the performance of market retribution of Serang city in the period of 2009 to 2015 is less well; (2) according to the perception of the merchants, the endeavor of the implementation of market service retribution is running quite well; and (3) the first priority of the strategy which can be implemented in improving market retribution is the issuance of technical guidelines concerning to the attainment of market retribution collection. Key Words: Market Retribution, Local Government Financial Performance, Strategy to Increase of Retribution Revenue, Serang City ABSTRAKEra otonomi daerah mengharuskan setiap daerah memiliki kemandirian dalam mengelola keuangan daerahnya untuk meningkatkan pendapatan asli daerahnya. Retribusi pelayanan pasar merupakan salah satu jenis retribusi yang potensial sebagai sumber pendapatan asli daerah. Kota Serang menjadi salah satu tujuan pedagang dari daerah lain untuk menjual dagangannya karena perkembangan perekonomian yang pesat. Penelitian ini bertujuan untuk: mengukur kinerja retribusi pelayanan pasar, menganalisis persepsi pedagang terhadap pelaksanaan pemungutan dan merumuskan strategi meningkatkan penerimaan retribusi pelayanan pasar. Data primer diperoleh dari wawancara dengan responden pedagang dan pejabat instansi terkait dipilih secara sengaja (purposive sampling). Metode analisis yang digunakan untuk masing-masing tujuan adalah: analisis kinerja keuangan daerah, analisis statistika deskriptif, dan proses hirarki analitik (analytical hierarchy process). Hasil dari masing-masing analisis menunjukkan bahwa: (1) secara umum kinerja retribusi pelayanan pasar Kota Serang tahun 2009 hingga 2015 kurang baik; (2) berdasarkan persepsi pedagang, upaya pelaksanaan pemungutan retribusi pelayanan pasar sudah berjalan cukup baik; dan (3) strategi prioritas pertama yang dapat diimplementasikan dalam peningkatan penerimaan retribusi pelayanan pasar adalah penerbitan petunjuk teknis pelaksanaan pemungutan retribusi pelayanan pasar.Kata Kunci: Retribusi Pelayanan Pasar, Kinerja Keuangan Pemerintah Daerah, Strategi Peningkatan Penerimaan Retribusi, Kota Serang